Growth of the Human Ilium: The Anomalous Sacroiliac Junction. Issue 11 (18th September 2013) - Yusof, Nurul A.; Soames, Roger W.; Cunningham, Craig A.; Black, Sue M.
ABSTRACT Despite the major anatomical importance of the human ilium in medicine and forensic investigations, little is understood about its pattern of growth. This study was conducted to investigate the changes in the surface area of the human ilium from birth through to adolescence in 80 human ilia. A photographic image of the pelvic surface of each bone was taken and examined using an image quantification package. The surface areas of four regions of interest were quantified: the auricular, post‐auricular (PA), iliac fossa, and whole pelvic surface of the ilium. The results highlight a rapid increase in surface area for all regions in the first few years after birth which continues, albeit at a slower rate, until ∼4 years of age when the rate of growth is further reduced. Although the ilium and its various components continue to grow between 5 years and puberty, the rate of growth is markedly reduced until puberty when growth of the pelvis again increases. Interestingly, analysis of the differential growth of the auricular region compared with the PA region throughout development suggests that the PA region exhibits more advanced growth. This may indicate that its role in structural development for the purposes of preparation and maintenance of bipedal stance and locomotion may have been previously poorly understood. Anat Rec, 296:1688–1694, 2013. © 2013 Wiley Periodicals, Inc.